DAYA PREDIKSI PAJAK, LABA DAN ARUS KAS TERHADAP PAJAK MASA DEPAN DENGAN VARIABEL KONTROL UKURAN PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2009 – 2014) - Ardi Hamzah (JAFFA, 2015)
The objectives of this researach are to examine prediction power of tax, earnings, and cash flow on future tax with firms size namely asset total and sales value as control variable. The samples of data are manufactur firm that listed in Indonesia Stock Exchange in period 2009 – 2014. Data total is 270 firm that fulfill requirement namely have not negative tax, earnings, and cash flow. The source of data is Indonesian Stock Exchange. Technic of data gathered is purposive sampling. The analysis that use in this research is statistic descriptif and regression test.The result of this research indicate that partially earnings, cash flow, and firm size namely asset total and sales value have significantly effect on tax future, while tax have not significantly effect on future tax. For examining simultantly indicate that tax, earnings, cash flow, and firm size have significantly effect on future tax. The prediction power earnings on future tax better than cahs flow and tax.